2023
DOI: 10.1111/sms.14355
|View full text |Cite
|
Sign up to set email alerts
|

Athletes with different habitual fluid intakes differ in hydration status but not in body water compartments

Abstract: Total body water (TBW) is divided into intracellular water (ICW) and extracellular water (ECW), and they have remarkable physiological functions such as transportation, thermoregulation, and participation in chemical reactions. 1 Thus, maintenance of a euhydrated state is crucial for the proper functioning of the body, with this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…< 35 ml/kg/d). Also, based on previous studies, (12,13,31,32) we expect some physiological differences between LOW and HIGH conditions. For example, it has been reported that LOW has a lower daily water intake (identified by food records), higher AVP, higher urine osmolality and urine specific gravity.…”
Section: Screening Processmentioning
confidence: 69%
“…< 35 ml/kg/d). Also, based on previous studies, (12,13,31,32) we expect some physiological differences between LOW and HIGH conditions. For example, it has been reported that LOW has a lower daily water intake (identified by food records), higher AVP, higher urine osmolality and urine specific gravity.…”
Section: Screening Processmentioning
confidence: 69%
“…Hydration status was not determined, for instance, by using urine-specific gravity, which means that it was not possible to ensure whether athletes were considered euhydrated. Nonetheless, a recent study aimed at comparing body water compartments and hydration status of athletes with different regular amounts of water intake (low vs. high water drinkers with higher and lower urine specific gravity values) found no differences in TBW and FFM hydration between groups for both sexes ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a weakly negative correlation between BIVA and USG has been found in divers, which is the opposite of what the authors expected, since such results indicated that the higher the amount of water, the higher the urine density [ 38 ]. In a recent study, Francisco et al [ 39 ] showed that athletes with a low water intake reported higher USG values. However, low and high water intake differences were found in no TBW, ICW, ECW and ECW/ICW ratio (all these parameters were determined using dilution techniques).…”
Section: Discussionmentioning
confidence: 99%